Disgust, Sadness, and Appraisal: Disgusted Consumers Dislike Food More Than Sad Ones - Motoki, Kosuke; Sugiura, Motoaki (Frontiers in Psychology, 2018)
According to the affect-as-information framework, consumers base judgments on their feelings. Disgust is associated with two kinds of appraisal: one in which the consumer avoids and distances him/herself immediately from the object concerned, and another in which the consumer is disgusted due to contamination and impurities within the environment. The first instance indicates that disgust can decrease a consumer’s preference for a product, regardless of its category. In contrast, the second case suggests that a product’s degree of depreciation is greater in products vulnerable to contamination, such as foods. However, it remains largely unknown how incidental disgust affects product preferences in accordance with the two appraisal-related goals. The present research investigates how incidental disgust (as opposed to sadness, an equally valenced but distinct emotion of appraisal) influences consumer preferences for products with or without a risk of contamination. Twenty-four participants repeatedly judged foods or household products after seeing an emotional image (conveying disgust, sadness, or neutrality). Foods and household products are the two representative product categories in grocery stores, but only foods are associated with a risk of contamination. The results showed that incidental disgust led to negative evaluations of both types of products; however, compared to sadness, incidental disgust demonstrated a stronger negative effect on preference for foods than household products. These findings elucidate that disgust and the appraisal of contamination specifically devalue foods, and broaden the application of the appraisal-information framework in consumer settings.